Lack of Association between Lactotransferrin Polymorphism and Dental Caries - Volckova, M.; Borilova Linhartova, P.; Trefna, T.; Vlazny, J.; Musilova, K.; Kukletova, M.; Kukla, L.; Izakovicova Holla, L. (Caries research, 2014)
Objective: Dental caries is a complex, multifactorial disease and one of the most common illnesses worldwide. Its etiology is related to microbial, dietary and host factors. Recent evidence suggests a role of lactotransferrin (LTF) in caries. The purpose of this study was to determine the association between LTF gene polymorphism and dental caries. Methods: In this case-control study, 637 unrelated children, aged 11-13 years, were enrolled. The subjects were divided into two groups, i.e. caries-free (decayed/missing/filled teeth = 0) and caries-affected children (decayed/missing/filled teeth ≥ 1). The LTF rs1126478 (140A/G in exon 2, Lys/Arg) genotypes were determined by PCR with restriction analysis using the EarI enzyme. Results: Of 637 children, 155 (24.3%) were caries free. There were no statistically significant differences between caries levels and allele or genotype distributions in the total cohort. When the caries-affected group (n = 482) was stratified into low (decayed/missing/filled teeth = 1), moderate (2 ≤ decayed/missing/filled teeth ≤ 3) and high (decayed/missing/filled teeth ≥ 4) caries experience, allele and genotype frequencies were similar among all subgroups. Conclusions: The LTF 140A/G (exon 2, Lys/Arg) polymorphism was not associated with the susceptibility to or severity of dental caries in the Czech population.